2010
DOI: 10.2134/agronj2009.0346
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Economic Assessments of Fertilizer Nitrogen and Phosphorus for Processing Tomato with Drip Fertigation

Abstract: Agronomic and economic assessments of response of processing tomato (Lycopersicon Esculentum Mill.) to nutrient application with drip fertigation are essential to optimize soil fertility management that maximizes farmers' profi tability in a sustainable manner. A fi eld study was conducted to evaluate the yield and economic responses of drip fertigated processing tomatoes to additions of fertilizer nitrogen (N) and phosphorus (P) from 2003 to 2005. Th e experiment was arranged in a factorial design with four l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 29 publications
2
27
1
2
Order By: Relevance
“…The highest tomato yield in drip is possible because water and fertilizers are applied in a gradual and uniform form directly to the roots, in sync with the crop demand, without wetting the plants (Hartz and Bottoms, 2009;Shedeed et al, 2009;Marouelli et al, 2011a). However, for a greater economic feasibility of the system, it is important to manage the entire production system properly, especially for irrigation and fertigation (Zhang et al, 2010). Tomato plants properly drip irrigated and fertigated by drip systems become more vigorous and productive, which requires a greater extraction of soil nutrients (Hartz and Bottoms, 2009).…”
Section: Tomatomentioning
confidence: 99%
See 1 more Smart Citation
“…The highest tomato yield in drip is possible because water and fertilizers are applied in a gradual and uniform form directly to the roots, in sync with the crop demand, without wetting the plants (Hartz and Bottoms, 2009;Shedeed et al, 2009;Marouelli et al, 2011a). However, for a greater economic feasibility of the system, it is important to manage the entire production system properly, especially for irrigation and fertigation (Zhang et al, 2010). Tomato plants properly drip irrigated and fertigated by drip systems become more vigorous and productive, which requires a greater extraction of soil nutrients (Hartz and Bottoms, 2009).…”
Section: Tomatomentioning
confidence: 99%
“…Thus, it is necessary to reevaluate the pre-established fertilization practices to maintain adequate fertility in the root zone (Hartz and Bottoms, 2009). Shedeed et al, (2009) andZhang et al, (2010) reported that the amount of nutrients required by a particular crop may be quite variable depending on its productive potential and the climatic and soil conditions. Hebbar et al, (2004) showed that fertigation with 100% water soluble fertilizers (WSF) increased the tomato fruit yield significantly over furrow irrigated control and drip irrigation.…”
Section: Tomatomentioning
confidence: 99%
“…A recent study recommended N fertilizer applications of 271 kg N ha -1 for drip fertigated processing tomatoes (Zhang et al 2010), approximately two times greater than previous N recommendations. In contrast, increased plant N use efficiency in tomato has been reported at lower fertilizer N rates with the application of fertilizer K (Fitzpatrick and Guillard 2004).…”
Section: Introductionmentioning
confidence: 86%
“…Processing tomatoes require adequate supplies of water and a proper balance of nutrients to achieve optimum yields (Patanè and Cosentino 2010; Zhang et al 2010). As described by Hartz and Bottoms (2009), nitrogen (N) uptake by drip-irrigated (DI) processing tomatoes varies from 222 to 466 kg N ha -1 .…”
Section: Introductionmentioning
confidence: 99%
“…Como a resposta das culturas à adubação fosfatada é fortemente influenciada pela capacidade de adsorção de P ao solo, novas pesquisas devem ser conduzidas em condições específicas de solo e de cultivo (Shedeed et al, 2009;Zhang et al, 2010;Rehim et al, 2012). Nesse contexto, não se encontraram estudos sobre métodos e formas de parcelamento da aplicação de P à cultura do tomate, em solos distróficos de Cerrado, que tenham associado a aplicação convencional ao sulco, em pré-plantio, à adubação complementar via fertirrigação por gotejamento.…”
Section: Introductionunclassified